Evaluation of Protocols for DNA Extraction from Individual Culex pipiens to Assess Pyrethroid Resistance Using Genotyping Real-Time Polymerase Chain Reaction - Ilaria Congiu; Elisa Cugini; Daniele Smedile; Federico Romiti; Manuela Iurescia; Valentina Donati; Claudio De Liberato; Antonio Battisti (Methods and Protocols)
Culex pipiens is a major vector of pathogens, including West Nile and Usutu viruses, that poses a significant public health risk. Monitoring pyrethroid resistance in mosquito populations is essential for effective vector control. This study aims to evaluate four DNA extraction protocols—QIAsymphony, DNAzol® Direct reagent, PrepMan® Ultra Sample Preparation Reagent (USPR), and Chelex® 100—to identify an optimal method to extract DNA from individual Culex pipiens, as part of a high-throughput surveillance of pyrethroid resistance using Real-Time Genotyping PCR. The target is the L1014F mutation in the voltage-sensitive sodium channel (VSSC) gene, which confers knockdown (kdr) resistance to pyrethroids. Mosquitoes were collected from wintering and summer habitats in Lazio and Tuscany, Italy, and DNA was extracted using the four methods. The quality, quantity, extraction time, and cost of the DNA were compared among the various methods. The PrepMan® USPR protocol was the most efficient, providing high-quality DNA with a 260/280 purity ratio within the optimal range at the lowest cost and in a short time. This method also demonstrated the highest amplification success rate (77%) in subsequent real-time PCR assays, making it the preferred protocol for large-scale genotyping studies.